The Impending Crisis - Raymond L. Kaplan (American Society for Microbiology, 2010)
When you are ill and consult a physician for his or her expertise, many times laboratory testing is part of the clinical workup. This testing is critical to the physician’s ability to diagnose the patient’s condition. What if testing was not available … because there was no one to do the testing? Although seemingly far-fetched, this scenario could play itself out in the next ten years due to an impending manpower crisis in laboratory medicine. The profession of Medical Technology, also known as Clinical Laboratory Science, is experiencing a shortage of qualified individuals for a variety of reasons – not the least of which is the closure of almost 70% of the schools teaching this critical profession. Health care workers (HCW) rely on accurate and timely clinical laboratory results in order to make decisions for their patients. Because ∼ 70% of patient care decisions are based on clinical laboratory results, it is important to have a well-trained supply of laboratory professionals. This article will give an overview of the situation and the possible causes of this shortage, and pose challenges to our profession as to how this crisis can be averted. Visibility of this profession must be a prime focus of this effort in order for the population in general to be aware of the role Clinical Laboratory Scientists play in the health care consortium. This effort should begin early in the educational process, potentially as early as Middle School (junior high school), bringing awareness of the profession not only to students but to educators as well.